(Invited)Point-of-Care Based System Development for Urolithiasis Recurrence Prevention. (10th April 2018) - Chung, Wen-Yaw; Heythem, Salhi; Silverio, Angelito; Tsai, Vincent; Cheng, Cheanyeh; Wu, Guan-Wei; Chang, Syuan-kai; Yen, Lin-Chen; Yang, Chia Ming; Lo, I-Wen; Chang, Shu-Yu
Abstract : This research presents a Point-Of-Care Test (POCT) system developed for urolithiasis recurrence prevention. The system can be used to assist a patient in assessing the condition of his urinary system through urine quality indicators pH, Ca 2+, uric acid, conductivity, etc. Several major types of sensors were used to monitor key parameters in human's urine. Ion Sensitive Field Effect Transistor and Extended Gate Field Effect Transistor potentiometric-type sensors are used for pH and Ca 2+ monitoring, the enzyme based two or three-electrode amperometric type sensor is used for urine's uric acid sensing, and the self-developed electrodes are used for conductivity measuring. The prototype with these sensors and CMOS readout circuits were integrated and tested in the laboratory and clinically. The test results show the acceptable and promising performance referred to corresponding meters for individual parameter sensing. Through the following data analysis and risk evaluation by urologists, the developed POCT system has a potential value and contribution to kidney stone of urolithiasis recurrence prevention.